The Truths/Fictions/Traumas of Marikana: Exploring Violence and Trauma in Three Films, The Marikana Massacre: Through The Lens (2013), Miners Shot Down (2014), and Night is Coming: A Threnody for the Victims of Marikana (2014). Issue 4 (2nd October 2018) - Scott, Claire
ABSTRACT: By exploring three films that centre on the Marikana strikes and killings of 2012, I seek to examine both the representations of violence as trauma, and the trauma of representing violence, within the context of visual, cinematic texts. I position Marikana, and the trauma of Marikana, as both a highly significant moment, and also as representative of deeper social and political traumas and injustices. I ask whether and how these films create a narrative context for this pivotal moment in South African history. I also question the effects of cinematic style and genre in the depictions of trauma and violence. The institutional context in which each film originated and developed is important, and I argue that the audience's expectations of the genre of documentary film also play a significant role in the way in which the films process trauma. I situate my paper in conversation with previous articles by Lucy Graham and Helene Strauss among others, that deal with cinematic portrayals of Marikana. By examining the selected films alongside each other, and through the lens of Decolonial Trauma Studies, I hope to elucidate the ways in which these South African films deal with and work through trauma.